Hyetograph simulation of high-intense rainfall events - Konecny, Franz, author; Strauss, Peter, author; Colorado State University, publisher (Colorado State University. Libraries, 2008)
The simulation of storm hyetographs is an important issue for various applications in hydrology and soil sciences. In this study we present a modification of the simple scaling model of Koutsoyiannis and Foufoula-Georgiou (1993), which assume a piecewise linear relationship between the logarithmic duration and logarithmic expected depth of an event. The expectation of the rainfall depth is estimated by local regression smoothing.
Hydrology days 2008
AGU hydrology days 2008
2008 annual AGU hydrology days was held at Colorado State University on March 26 - March 28, 2008.